A scoping review exploring oral health inequalities in India: a call for action to reform policy, practice and research - Parul Dasson Bajaj; Ramya Shenoy; Latha Sanjay Davda; Kundabala Mala; Gagan Bajaj; Ashwini Rao; Aparna K.S; Mithun Pai; Praveen Jodalli; Avinash B.R (BMC, 2023)
Abstract Introduction Reduction in health inequalities and providing universal access to health care have been identified as two important global milestones by the World Health Organization for countries to achieve by 2030. Therefore, recognizing the magnitude of oral health inequalities in India has become a pressing priority to improve access to dental care within the country. This scoping review was conducted with the aim of reviewing, collating and analysing the current knowledge base on oral health inequalities in India. Methodology The scoping review followed Arksey and O'Malley's approach, and reporting was performed in accordance with the PRISMA-ScR guidelines. A systematic search was conducted on Scopus, PubMed, Web of Science, and EMBASE to identify literature addressing one or more dimensions of oral health inequalities in India, published in English between January 2002 and April 2022. The data were charted, and qualitative analysis was performed to derive themes, highlighting the key concepts emerging from this review. Results In accordance with the eligibility criteria, a total of 71 articles retrieved through database search and backward citation search were included in this scoping review. The major themes ranged from individual to diverse sociodemographic factors acting as barriers to and facilitators of access to dental care. Deficiencies in human resources for oral health, along with a wide diversity in dental service provision and dental education were other major themes contributing to inequality. Subsequently, this has resulted in recommendations on restructuring the dental workforce and their development and modifications in oral health care policies and practices. The qualitative synthesis demonstrates the intertwined nature of the multiple factors that influence the goal of achieving an affordable, accessible, extensive and inclusive oral healthcare system in India. Conclusions This comprehensive review provides a broad perspective on oral health inequalities in India, providing valuable insights for both researchers and policymakers in this area and guiding their efforts towards achieving universal oral health coverage in the Indian context.